Invasive technification : critical essays in the philosophy of technology - Böhme, Gernot (Bloomsbury Academic, 2012)
Technology has extended its reach to the human body - not just in a literal sense, through implants, transplants and technological substitutes for biological organs, but in a more figurative sense too. Technological infrastructure and the instutions of a technified society today determine what perception is, how we communicate and what forms of social life are possible. A fundamental new conception of technology is therefore required. Technology can no longer be seen simply as a means of efficiently attaining pre-established ends. Rather, it needs to be considered as a total structure, somethi.